Succinct review of MBDR/BDR technique in reducing ship's drag. (21st October 2021) - Sindagi, Sudhir; Vijayakumar, R.
ABSTRACT: Reducing the ship's drag is an effective technique for reducing emissions, operating expenses, and improving EEDI. For slow-moving vessels, frictional resistance has been reported to contribute up to 80% of total resistance, demanding a thorough investigation in reducing it. Air or the gas has been used as a lubricant, to reduce the frictional resistance known as Micro Bubble Drag Reduction, which is the need of a present era. In this paper, the current research scenario on the technique is presented, which suggests a plausible reduction in frictional resistance of 80% for ships. The review suggests that reduction in drag depends on void fraction, coalescence and breaking of injected bubbles, the salinity of water and type of gas used, depth of water in which the bubbles are injected, and of course, on the location of injection points. In the end, recommendations have been provided to improve the drag reduction.